2011
DOI: 10.1038/ncb2222
|View full text |Cite
|
Sign up to set email alerts
|

RNF146 is a poly(ADP-ribose)-directed E3 ligase that regulates axin degradation and Wnt signalling

Abstract: The Wnt/β-catenin signalling pathway plays essential roles in embryonic development and adult tissue homeostasis, and deregulation of this pathway has been linked to cancer. Axin is a concentration-limiting component of the β-catenin destruction complex, and its stability is regulated by tankyrase. However, the molecular mechanism by which tankyrase-dependent poly(ADP-ribosyl)ation (PARsylation) is coupled to ubiquitylation and degradation of axin remains undefined. Here, we identify RNF146, a RING-domain E3 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
480
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(489 citation statements)
references
References 29 publications
8
480
0
1
Order By: Relevance
“…Recent studies have demonstrated that ARTD5-and 6-(formerly Tankyrase1 and 2) dependent PARylation of axin results in the recruitment of the ubiquitin E3 ligase RNF146 and subsequent pUb-dependent proteasomal degradation of axin, a negative regulator of WNT signalling 9,10,25 . Similarly, 3BP2 is substrate of ARTD5 and RNF146.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that ARTD5-and 6-(formerly Tankyrase1 and 2) dependent PARylation of axin results in the recruitment of the ubiquitin E3 ligase RNF146 and subsequent pUb-dependent proteasomal degradation of axin, a negative regulator of WNT signalling 9,10,25 . Similarly, 3BP2 is substrate of ARTD5 and RNF146.…”
Section: Discussionmentioning
confidence: 99%
“…PARylation regulates various cellular processes, such as DNA repair, specific signalling processes and gene transcription 5 . The functional consequences of PARylation are mediated by distinct protein domains, including macrodomains, WWE (named after two conserved tryptophan residues and a glutamate residue) and PAR-binding zinc-finger (PBZ) domains [6][7][8][9][10] . In contrast to the function of class 1 ARTD enzyme-mediated PARylation, little is known about the biological relevance of mono-ADP-ribosyltransferases.…”
mentioning
confidence: 99%
“…The stabilities of Axin and Dishevelled, an upstream positive component of the pathway, are regulated by the E3 ligase activities of RNF146 and KLHL12, respectively. The KLHL12-mediated proteasomal degradation of Dishevelled is a Wnt-regulated event, but it is unclear whether the same is true of RNF146-mediated Axin degradation (15)(16)(17). Like KLHL12, the recently described ZNRF3 represents another E3 ubiquitin ligase that negatively regulates proximal events in the Wnt pathway.…”
mentioning
confidence: 99%
“…1D). We suspect that the high-molecular-weight smears of co-precipitated endogenous and Myc-Axin (AXIN1 * ), could represent PARsylated/K48-polyubiquitylated populations that have accumulated in MG132-treated cells (28,30). The total precipitated APC pool also resolved with a retarded electrophoretic mobility (APC * ), as revealed by immunoblotting with a rabbit polyclonal APC antibody (clone H-290), but the reason for this is unclear (Fig.…”
Section: Wnt3a-mediated Loss Of K63-polyubiquitin Adducts From Apc Rementioning
confidence: 99%
“…K48-linked adducts controls not only the stability of ␤-catenin, but also that of several Wnt pathway components including Axin, Dvl, and APC (27)(28)(29)(30). Interestingly, Dvl and APC are also modified with K63-linked ubiquitin chains, as inferred from loss-of-function studies of the deubiquitylating enzymes CYLD and Trabid, respectively (31,32).…”
mentioning
confidence: 97%